PENGARUH STRUKTUR KEPEMILIKAN TERHADAP COST OF CAPITAL DENGAN VOLUNTARY DISCLOSURE SEBAGAI VARIABEL INTERVENING - Fenny Apriliani; Puji Harto (Diponegoro Journal of Accounting, 2016)
The number of failures experienced by large companies that make the cost of equity and cost of debt increases, prompting investors to pay more attention to corporate governance and the level of voluntary disclosure. The purpose of this study was to analyze the family ownership and institutional ownership on the level of voluntary disclosure and its impact on the cost of equity and cost of debt of companies in the mining company listed on the Stock Exchange in 2011-2014. The study population was the whole financial data of companies listed on the Stock Exchange 2011-2014 period. The sampling method used in this research is purposive sampling method. The sample used in this study are listed on the Stock Exchange of mining in berutur respectively in 2011-2014. The data used are secondary data from BEI. The analysis technique used is path analysis. Based on this research, family ownership and institutional ownership positively affects Voluntary disclosure. Institutional ownership and voluntary disclosure positive effect on the equity fee, but the family does not affect the ownership of the equity fee. Family ownership does not affect the fee payable. Institutional ownership positively affects the debt fee. Voluntary disclosure negatively affect debt Fees.